2018
DOI: 10.3389/fpsyg.2018.01775
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Efficacy of Training Basic Numerical Cognition and Transfer Effects to Improvement in Children’s Math Ability

Abstract: The goals of the present study were to test whether (and which) basic numerical abilities can be improved with training and whether training effects transfer to improvement in children’s math achievement. The literature is mixed with evidence that does or does not substantiate the efficacy of training basic numerical ability. In the present study, we developed a child-friendly software named “123 Bakery” which includes four training modules; non-symbolic numerosity comparison, non-symbolic numerosity estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 61 publications
(114 reference statements)
1
8
0
Order By: Relevance
“…For complex word reading fluency, no differences between the conditions were observed. The mixed results with respect to far transfer are in line with previous DGBL research which also reported mixed findings on far transfer tests for math and reading immediately after the intervention (e.g., Kartal & Terziyan, 2016;Kim et al, 2018;Obersteiner et al, 2013;van Gorp et al, 2017).…”
Section: Socio-economic Status (Ses)supporting
confidence: 87%
See 2 more Smart Citations
“…For complex word reading fluency, no differences between the conditions were observed. The mixed results with respect to far transfer are in line with previous DGBL research which also reported mixed findings on far transfer tests for math and reading immediately after the intervention (e.g., Kartal & Terziyan, 2016;Kim et al, 2018;Obersteiner et al, 2013;van Gorp et al, 2017).…”
Section: Socio-economic Status (Ses)supporting
confidence: 87%
“…Several empirical studies used DGBL to improve early numerical skills. Kim, Jang, and Cho (2018) randomly assigned 56 first graders to an experimental condition (training numerical processing) or a control condition (following regular education). The experimental condition outperformed the control condition in non-symbolic comparison, but not in other early numerical skills (e.g., approximate arithmetic).…”
Section: Dgbl In Early Mathmentioning
confidence: 99%
See 1 more Smart Citation
“…Counting is required for a large number of daily activities and is often implicated in more complex calculations and mathematical tasks [33]. In this respect, serial counting could be considered a basic ability in people's daily lives.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies assert that comprehension of the nonsymbolic number concept provides a foundation for the symbolic math skills [17,37,48]. To that end, recent interventions that train NSM abilities showed children's progress in comparing ratios as well as how this progress also reflected on their symbolic math skills [6,36,45,46].…”
Section: Nonsymbolic Mathmentioning
confidence: 99%